A review: The detection of cancer cells in histopathology based on machine vision. (July 2022) - He, Wenbin; Liu, Ting; Han, Yongjie; Ming, Wuyi; Du, Jinguang; Liu, Yinxia; Yang, Yuan; Wang, Leijie; Jiang, Zhiwen; Wang, Yongqiang; Yuan, Jie; Cao, Chen
Abstract: Machine vision is being employed in defect detection, size measurement, pattern recognition, image fusion, target tracking and 3D reconstruction. Traditional cancer detection methods are dominated by manual detection, which wastes time and manpower, and heavily relies on the pathologists' skill and work experience. Therefore, these manual detection approaches are not convenient for the inheritance of domain knowledge, and are not suitable for the rapid development of medical care in the future. The emergence of machine vision can iteratively update and learn the domain knowledge of cancer cell pathology detection to achieve automated, high-precision, and consistent detection. Consequently, this paper reviews the use of machine vision to detect cancer cells in histopathology images, as well as the benefits and drawbacks of various detection approaches. First, we review the application of image preprocessing and image segmentation in histopathology for the detection of cancer cells, and compare the benefits and drawbacks of different algorithms. Secondly, for the characteristics of histopathological cancer cell images, the research progress of shape, color and texture features and other methods is mainly reviewed. Furthermore, for the classification methods of histopathological cancer cell images, the benefits and drawbacks of traditional machine vision approaches and deep learning methods are compared and analyzed. Finally, the above research is discussed and forecasted, with the expected future development tendency serving as a guide for future research. Highlights: A review of machine vision in cancer cell detection methods. Analyze the main points of histopathological image preprocessing and put forward key issues in the future. Research and summarize the influence of various image segmentation methods of histopathology. Summarized the mainstream research methods of feature extraction. Proposed improvement methods for classification and proposed future development directions.